2005
DOI: 10.1002/ajhb.20411
|View full text |Cite
|
Sign up to set email alerts
|

Does milk make children grow? relationships between milk consumption and height in NHANES 1999-2002

Abstract: In the United States, milk (usually cow's milk) is widely considered an "essential food" to support bone growth among post-weaning age children, as evident in government-sponsored nutrition policies that mandate milk for children. Milk contains calories, protein, and calcium, among other nutrients, and bioactive components such as insulin-like growth factor-I (IGF-I), all of which may facilitate bone growth. There is a large literature on milk and/or calcium intake and its effects on bone density, but one aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 47 publications
5
78
0
3
Order By: Relevance
“…81 Similarly, milk consumption was positively associated with adult height among a nationally representative sample from the United States. 82 In particular, increased consumption of cow's milk is associated with linear growth, 83 although there may be something specific to milk itself besides milk protein. One trial in India showed that children born within a community-based intervention offering nutrition supplementation during pregnancy and early childhood were 14 mm taller than the control group and had a reduced risk of cardiovascular disease upon reaching adolescence.…”
Section: Nutritionmentioning
confidence: 99%
“…81 Similarly, milk consumption was positively associated with adult height among a nationally representative sample from the United States. 82 In particular, increased consumption of cow's milk is associated with linear growth, 83 although there may be something specific to milk itself besides milk protein. One trial in India showed that children born within a community-based intervention offering nutrition supplementation during pregnancy and early childhood were 14 mm taller than the control group and had a reduced risk of cardiovascular disease upon reaching adolescence.…”
Section: Nutritionmentioning
confidence: 99%
“…Research that has studied the influence of milk on growth potential suggests that milk supplementation has the most impact on the growth of undernourished children (Wiley 2005 As reviewed in Chapter 2, the distribution of radiocarbon dates from sites with domestic stock supports Elphick's (1977) proposal concerning the southward movement of sheep from the Zambezi region to the Cape. However, …”
Section: Skeletal Evidence Of Diffusionmentioning
confidence: 70%
“…More precisely, a positive correlation was found between the dairy intake and height in those children who were A-allele carriers for the IGF2 polymorphism. Results from the NHANES study (Wiley, 2005) indicated that adult height was positively associated with milk consumption at ages 5-12 and 13-17 years, after controlling for sex, education and ethnicity. The strongest evidence that milk and dairy product intake stimulate linear growth comes from observational and intervention studies in developing countries that show considerable effects.…”
Section: Discussionmentioning
confidence: 99%